Orally Administered Nanoparticle Coacervate for Therapeutic Coating of Full Gastrointestinal Tract - Lee, Yunjung; Kim, Youngjoon; Kwon, Seokjun; Park, Ok Kyu; Min, Gyeong Ho; Chu, Jinyoung; Kim, Yubeen; Yoon, Johyun; Lee, Hyochul; Kim, Hojun; Soh, Min; Lee, Nohyun; et al. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2026)
Oral delivery of therapeutic nanoparticles offers a non-invasive approach for treating gastrointestinal diseases, but achieving localized and sustained mucosal exposure while avoiding systemic toxicity remains a major challenge. Here, a Sucralfate-based oral formulation is developed that incorporates therapeutic nanoparticles and transforms into a paste-like coacervate upon contact with intestinal fluid, uniformly coating the entire gastrointestinal tract within 6 h, and clearing through fecal transit by 12 h. Systematic investigation shows that nanoparticle hydrophobicity is essential for stable incorporation into Sucralfate-based formulation, supporting compatibility with a wide range of nanoparticle types. The incorporated nanoparticles are stabilized by strong non-covalent interactions, which limit gastric leaching and reduce cellular uptake by 0.044% compared with PEGylated nanoparticles. As a representative example, antioxidant cerium oxide nanoparticles are tested in two distinct oxidative stress-related models of intestinal injury, including immune-mediated colitis and radiation-induced enteropathy. In DSS colitis, our system reduced weight loss from 17.2% to 2.2% and restored colon structure and oxidative-stress injury. In radiation-induced enteropathy, our system attenuated weight loss from 25.5% to 11.4%, doubled villus length, and markedly enhanced epithelial regeneration. The formulation also accommodates nanoparticles with imaging capability, demonstrating versatility for both therapeutic and diagnostic applications in gastrointestinal diseases.